The wheel of time the shamans of ancient Mexico, their thoughts about life, death and the universe - Castaneda, Carlos 1931-1998 (New York, NY Washington Square Press, publication of Pocket Books, 2001)
Contains a selection of quotations, collected by the author from his works on his training as a shaman initiate, including "The Teachings of Don Juan," "Journey to Ixtlan," " A Separate Reality," and "Tales of Power."
Quotations from The teachings of Don Juan -- Commentary -- Quotations from A separate reality -- Commentary -- Quotations from Journey to Ixtlan -- Commentary -- Quotations from Tales of power -- Commentary -- Quotations from The second ring of power -- Commentary -- Quotations from The eagle's gift -- Commentary -- Quotations from The fire from within -- Commentary -- Quotations from The power of silence -- Commentary.
Keywords: Juan -- Don -- 1891-1973.; Castaneda, Carlos -- 1931-1998.; Shamanism -- Mexico; Indians of Mexico -- Religion; Indigenous peoples -- Mexico -- Religion; Mexico -- Religion